Resource Potential of Waste Usage as a Component of Environmental and Energy Safety of the Sate - BEREZYUK, Sergiy; TOKARCHUK, Dina; PRYSHLIAK, Natalia (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
The article is devoted to the study of the resource potential of the use of waste as a component of the environmental and energy security of the state. The problem of handling solid waste is the most urgent component of ensuring national security for Ukraine, since the volumes of accumulated waste are considered as one of the factors of the progressive environmental crisis. The sphere of secondary use of resources in Ukraine is at the stage of active formation. Due to insufficient consideration of the value of secondary resource potential, lack of awareness and lack of proper marketing, underestimation of social (for example, creation of additional jobs) and environmental factors, and also due to mismanagement, a significant part of the waste that can be used as material and energy resources is lost. The purpose of the article is to assess the potential of waste use in order to form the state’s environmental and energy security. The readiness of the citizens of Ukraine for separate collection of household waste was analyzed. The number of landfills and their area in Ukraine were determined. Technologies for the processing of municipal solid waste were characterized. The benefits of sorting and recycling solid waste were analyzed. The hierarchy of waste management priorities in the EU was built. The cost of processing recyclable materials was analyzed. An analytical assessment of the resource potential of production and consumption waste was made. Priority areas for their use have been identified. A comparative analysis of inertial and innovative scenarios for the development of the field of waste management in Ukraine for the period up to 2025 was carried out. Estimated amount of biogas that can be obtained from the annual volume of buried solid household waste was determined. SWOT analysis of implementation of the project for collecting and utilizing biogas of solid waste dumps was carried out. Proposals for improvement of the waste management structure at the state level were presented.